Medial epiphyseal fracture-detachment of the sternoclavicular joint with posterior displacement in a judo athlete - equivalent of posterior sternoclavicular dislocation - Rui Pimenta; Nuno Alegrete; Vítor Vidinha; Sara Lima; Isabel Pinto (Revista Brasileira de Ortopedia, 2013)
Posterior sternoclavicular dislocation is a rare traumatic injury that presents a potential risk of injury to mediastinal structures. The diagnosis is fundamentally clinical and treatment is done on an emergency basis. The authors report the clinical case of a young judo athlete with post-traumatic medial epiphyseal fracture-detachment, with posterior displacement (lesion equivalent to posterior sternoclavicular dislocation at pediatric ages). He underwent open reduction and ligament repair by means of a mini-anchor.The radiological and clinical outcome was excellent, and the athlete returned to his sports activity without limitations. We discuss the particular features of this pathological condition, along with the different therapeutic approaches and their complications